Respostas
respondido por:
1
Oi Saitou
vamos colocar as equações sobre a forma ax + by = c
2*(x + 1) - 3*(y + 2) = x
2x + 2 - 3y - 6 - x = 0
x - 3y = 4 (I)
x/4 - (y - 1)/2 = -2
x/4 - 2*(y - 1)/4 = -8/4
x - 2y + 2 = -8
-x + 2y = 10 (II)
sistema
x - 3y = 4 (I)
-x + 2y = 10 (II)
adição
-y = 14
y = -14
-x - 28 = 10
-x = 38
x = -38
S = (-38, -14)
.
vamos colocar as equações sobre a forma ax + by = c
2*(x + 1) - 3*(y + 2) = x
2x + 2 - 3y - 6 - x = 0
x - 3y = 4 (I)
x/4 - (y - 1)/2 = -2
x/4 - 2*(y - 1)/4 = -8/4
x - 2y + 2 = -8
-x + 2y = 10 (II)
sistema
x - 3y = 4 (I)
-x + 2y = 10 (II)
adição
-y = 14
y = -14
-x - 28 = 10
-x = 38
x = -38
S = (-38, -14)
.
Saitou:
Por que na segunda equação vc inverteu os sinais deixando o x negativo?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás